Wong's nursing care of infants and children - Hockenberry, Marilyn J 4 0 16; 1950 August 25-2015;1948-2008 Wilson, David,;Barrera, Patrick;Wong, Donna L.; 5 (St. Louis : Mosby/Elsevier, 2007)
Accompanying CD-ROM contains interactive applications to make learning fun. It includes NCLEX review questions, pediatric assessment video clips, animations, critical thinking questions, case studies, assessment tools, and more
Donna L. Wong is the main entry of the previous ed
Includes bibliographical references and index
System requirements for accompanying computer disc: Windows: 486, Pentium, or faster processor, Windows 95, 98, NT, 2000, ME, XP, or higher; 64 MB RAM; 8x or faster CD-ROM drive, VGA monitor supporting thousands of colors (16 bit) or Macintosh
Keywords: 2 -- 0; 6; Pediatric nursing -- 20; 20; 2